PENGARUH LATIHAN SKIPPING TERHADAP HASIL LOMPATAN PEMAIN BOLA VOLI CLUB BANGKIT PUTRA - Syarul Luken Firdaus; Dadan Muldan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
THE EFFECT OF SKIPPING TRAINING ON THE JUMPING RESULTS OFCLUB BANGKIT PUTRA VOLLEYBALL PLAYERS. This study aims todetermine the effect of skipping training on the jumping results of Club Bangkit Putravolleyball players. The research method used was an experiment with a one-grouppretest-posttest design. The study subjects were 15 volleyball players whoparticipated in a four-week training program with a frequency of three meetings perweek. The data collection instrument used was a vertical jump test. The resultsshowed a significant increase in players' jumping ability, with an average pretest scoreof 33.4 increasing to 41.6 in the posttest. The paired sample t-test obtained asignificance value of 0.000 (<0.05), indicating a significant effect of vertical jumptraining on jumping ability. Thus, this training method has proven effective inimproving basic jumping skills in volleyball.